PENERAPAN AUGMENTED REALITY PENGENALAN NAMA ILMIAH FLORA DAN FAUNA BERBASIS ANDROID - Promega, Dikna Sella; Hutabri, Ellbert (Computer Science and Industrial Engineering, 2021)
The rapid development of today greatly affects most parts of individuals' lives in different area, particularly in the training area, one of them is utilizing Augmented reality learning media. Augmented reality permits clients to see this present reality with virtual articles. In this way. Augmented reality can be utilized as a learning media utilized by instructors to make it simpler for understudies to comprehend the learning material introduced. The porpose of this exploration is to build understudies' revenue in learning and perceive logical names of widely varied vegetation. The plan of Augmented reality utilizes the Makerless-Based Following strategy which is a technique that doesn't need a marker to show virtual articles. Scientists use UML to portray how the Augmented reality application functions, which comprises of 4 sorts of graphs, which is utilizing Case Outlines, Movement Charts, Arrangement Outlines, and Class Charts. In this examination, specialists utilized Solidarity 3D programming for application plan. Specialists likewise use Adobe Artist as an application plan. The aftereffects of this examination are that the application can be introduced on an Android gadget and the presence of this application is not difficult to utilize